CLASSIFICATION OF EUPHEMISMS IN THE POLITICAL DISCOURSE - Амирова, Е.Л. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2015)
The article presents the definitions of notions “discourse”, “political discourse”, “euphemisms”. The peculiarities of political discourse and euphemisation are explored. Various approaches to classify the political euphemisms are studied.
Keywords: discourse; political discourse; euphemisms; peculiarities of euphemisms